COVID-19 in Northeast Brazil: preliminary characteristics of deaths (Research, Society and Development, 2020)
Objective: to describe the characteristics of deaths in the Northeast region of Brazil. Methods: a descriptive study based on epidemiological bulletins released by the health departments of each state in the Northeast on the cases of COVID-19, until July 20, 2020, the mortality rate was calculated, a set of deaths aged over 60 years , sex and presence or not of comorbidity, in addition to an individual analysis by state of the most common associated diseases. Results: Ceará was the state with the most cases and deaths, and Piauí the least number of cases and deaths, the region's mortality rate is 3.6%. Most deaths in the region were composed of men with more 60 years old, with some associated comorbidity, mainly cardiovascular diseases, followed by diabetes mellitus. Conclusion: the features show similarities in comparison with the seen preliminary results in other locations around the world.